Up-regulation of the Ang II/AT1 receptor may compensate for the loss of gastric antrum ICC via the PI3k/Akt signaling pathway in STZ-induced diabetic mice. (5th March 2016) - Zhang, C.M.; Huang, X.; Lu, H.L.; Meng, X.M.; Liu, D.H.; Kim, Young-chul; Xu, W.X.
Abstract: The classic renin–angiotensin system (RAS) is a complex system in which angiotensin II (Ang II) has been identified as an important endogenous regulator that influences both smooth muscle contraction and cell growth. Although a local RAS is known to exist in the gastrointestinal tract, it is unclear whether Ang II is involved in the loss of gastric interstitial cells of Cajal (ICC) in diabetic mice. The present study was designed to investigate the effect of Ang II on ICC survival in streptozotocin (STZ)-induced diabetic mice. Western blot, immunofluorescence, isometric muscle recording, enzyme-linked immunosorbent assay (ELISA) and a cell counting kit-8 were used in this research. Our results demonstrate that the c-Kit and membrane-bound stem cell factor (mSCF) protein expression levels in gastric smooth muscle were decreased in STZ-induced diabetic mice. However, the angiotensin receptor type 1 (AT1R) expression levels in gastric smooth muscle and angiotensin-converting enzyme (ACE) expression levels in gastric mucosa were increased. The effect of Ang II on the tonic contraction of gastric smooth muscle was potentiated in diabetic mice, and the plasma Ang II level was enhanced. Ang II increased mSCF expression, cell proliferation, and Akt-Ser473 phosphorylation in cultured gastric smooth muscle cells (GSMCs). These effects were reduced by specific inhibitors ZD7155 (an AT1R antagonist) and LY294002 (a PI3-kinase inhibitor). Our results suggest that Ang II increases mSCF expression and cell proliferation in cultured GSMCs in a PI3K/Akt signaling-dependent manner. ACE and AT1R up-regulation in the stomach may help compensate for ICC loss in STZ-induced diabetic mice. Highlights: ICC number and mSCF were decreased in gastric antrum of STZ-induced diabetic mice. Local RAS could be activated in the gastric antrum of STZ-induced diabetic mice. Up-regulation of local RAS in gastric antrum may compensate for ICC loss in diabetic. Ang II induced gastric smooth muscle cell proliferation and mSCF expression in vitro. The effects of Ang II may be mediated by PI3k/Akt signaling pathway.